Increasing the Durability and Freeze-Thaw Strength of Concrete Paving Stones Produced from Ahlat Stone Powder and Marble Powder by Special Curing Method - Abdulrezzak Bakis (Advances in Materials Science and Engineering)
This study highlights an investigation of using construction waste materials, i.e., Ahlat stone powder and marble powder, in fabricating interlocked paving stones. In this study, the durability and freeze-thaw strength of concrete paving stones produced from Ahlat stone powder and marble powder were increased by the special curing method. Six different types of paving stones were fabricated for study and were subjected to two different curing regimes. Tests of water absorption, splitting tensile strength, surface abrasion, and freeze-thaw were carried out for the specimens. In 3 days and at 20 ± 5°C of water curing, the splitting tensile strength was 3.7 MPa, the surface abrasion value was 9.8 cm3/50 cm2, and the freeze-thaw value was 0.39 kg/m2 for those interlocked paving stones produced from Ahlat stone powder. After special combined curing, these improved to 3.9 MPa, 17.2 cm3/50 cm2, and 0.63 kg/m2, respectively. Accordingly, for interlocked paving stones produced from marble powder, in 3 days and at 20 ± 5°C water curing, the splitting tensile strength, surface abrasion, and freeze-thaw were 3.9 MPa, 7.9 cm3/50 cm2, and 0.34 kg/m2, respectively. After special combined curing, these values improved to 4.1 MPa, 14.8 cm3/50 cm2, and 0.57 kg/m2, respectively. The findings of this study validate increase in durability and freeze-thaw strength of concrete paving stones with special curing.